(untitled) (Linguostylistic Studies, 2016)
The article describes the lingvo-stylistic characteristic features of Ivan Vyshenskyi’s works, laying emphasis on such a feature of his linguistic creativity as appellative nomination of persons. The subject matter of the research is the literary heritage of the writer-polemicist, an outstanding religious figure, a significant page in the history of the Ukrainian literary language. The study presents the analysis of the motivational aspect of word building peculiarities of the lexical system in the works by Ivan Vyshenskyi. The study gives the grounds to conclude that the combination of traditional bookish and folk elements has determined the specificity of the onomastic system in the refined literary heritage of Ivan Vyshenskyi. Having utilized the word formation richness of the then Ukrainian language, the writer created occasionalisms of various word-building models and masterfully introduced borrowed lexical units into the vocabulary stock of his works. Key words: diachronic aspect, polemical style, nomination, thematic groups of vocabulary, semantics, onomasiology, derivation, word building types, word building models, native lexical items, borrowings. References